One-step methylation of aromatic phosphorus heterocycles: synthesis and crystallographic characterization of a 1-methyl-phosphininium salt. Issue 75 (19th August 2021) - Fischer, Lukas; Wossidlo, Friedrich; Frost, Daniel; Coles, Nathan T.; Steinhauer, Simon; Riedel, Sebastian; Müller, Christian
Abstract : By using the dimethyl chloronium salt [(CH3 )2 Cl] + [Al(OTeF5 )4 ] − in combination with the weakly coordinating pentafluoro-orthotelluratoaluminate anion it is possible to quaternize the phosphorus atom of a series of λ 3, σ 2 -phosphinines in one step. Abstract : For the first time, the direct synthesis of 1-methyl-phosphininium salts has been achieved by reacting aromatic λ 3, σ 2 -phosphinines with the readily available dimethyl chloronium salt [(CH3 )2 Cl] + [Al(OTeF5 )4 ] − . The remarkably high electrophilicity of the alkylation reagent in combination with the weakly coordinating pentafluoro-orthotelluratoaluminate anion offers excellent conditions for this one-step approach. Our simple and quantitative access to 1-methyl-phosphininium salts will pave the way to explore the chemistry of such reactive species in more detail.